Casa Tipica - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo la fachada de una casa tipica.
ENGLISH: The facade of a typical house was observed.

SPANISH: Se observo la fachada de una casa tipica.
ENGLISH: The facade of a typical house was observed.
Typical House
Keywords: Iquitos (Perú)|~|Amazonas (Peru)|~|Amazonas|~|Casa Rural|~|Amazonas (Peru)|~|Rural|~|Houses|~|Amazonas (Peru)|~|Amazonas|~|Casa Rural|~|Amazonas (Perú)|~|Casa Rural|~|Amazonas (Peru)|~|Amazonas|~|Casa Rural|~|Amazonas (Peru)|~|Rural House